Development of a system to detect hidden information in a document using steganography software - Wuan, Neng Jie (2018)
Steganography is the art of hiding secret information in plain sight. Manipulating the least significant bit (LSB) of the image’s pixel values is one of the most popular steganographic embedding method. This report documents the steps and development process of a software system that implements a signature-based steganalysis approach based on Patterns of Pixel Differences and Random Embedding. Like other blind steganalysis attempts, there will be inherent uncertainties and does not guarantee 100% detection rates. The accuracy of detection depends on the trained Support Vector Machine (SVM) model used, and therefore, accuracy hinges on the type of training data and test images used. Ultimately, there is no universal model that can provide effective classification for any type of image.